The Psychological Motivations to Social Innovation and Transmitting Role of Social Worth - Lin, Mei-Lan; Yu, Tai-Kuei; Sadat, Andi Muhammad (Frontiers in Psychology, 2022)
Social innovation has a great chance to overcome problems in complex environments. Individuals’ concern for environmental, social, and ethical issues has gradually grown, prompting the rise of new types of consumers, who shift their environmental concerns into action. social entrepreneurship participants mostly act as beneficiaries and initiators in the process of social innovation. Social exchange theory explains the linkage between individual psychological factors and personal social cognitive perceptions that inspire social innovation intention. The current research framework is constructed to inspect the individual mental process of psychological motivation associated with social innovation intention. The purpose is to understand the relationships between the psychological level of moral idealism, ecological concern, and prior experience on cognitive perceptions of social worth; subsequently, social worth, prosocial motivation, perspective-taking and positive feelings are examined to discover their influence on social innovation behavioral intention. The transmitting role of social worth exercises a transformative function between participants’ psychological motivation, social cognition, and social innovation intention. The research is conducted using PLS analysis software. The research results reinforce our understanding of theories of individual psychological motivations on social innovation. The findings also offer some suggestions for sustainability education to social enterprise practitioners with respect to recruiting young people and continuing to generate new ideas.